Microstructure characterization of high temperature mechanisms in a Nb–Ti–Si alloy. (May 2022) - Reyes, David; Malard, Virgil; Drawin, Stefan; Couret, Alain; Monchoux, Jean-Philippe
Abstract: The deformation mechanisms of an Nb–20Si–25Ti–6Al–3Cr–3Mo alloy deformed in compression at 1000 °C and at a strain rate of 10 −4 s −1 have been investigated, using focused ion beam and transmission electron microscopy techniques. The initial microstructure of the alloy was constituted of a solid solution bcc Nbss matrix and of Nb5 Si3 phases of β (tetragonal) and γ (hexagonal) crystallographic structures, with also hcp-Ti precipitates. As expected, the only phase which exhibited plastic deformation at 1000 °C was the Nbss matrix. Glide of b → = 1 / 2111 dislocations has been observed, in planes compatible with {112} and {123} planes, or with cross-slip in {110} planes, as classically reported in bcc structures. Conversely, climb contribution has not been evidenced, probably because of rearrangement of the climbing dislocations in sub-boundaries. Fine δ-Nb11 Si4 precipitates have been detected in the samples compressed at 1000 °C. Interactions of the δ-Nb11 Si4 precipitates with the dislocations have been observed, which can potentially lead to strengthening of the Nbss phase. Highlights: Microstructure and deformation mechanisms at 1000 °C of a Nb–Si–Ti alloy are investigated. TEM thin foils are extracted by FIB. Dislocation glide has been evidenced, climb could not be detected.